2020
DOI: 10.1177/0263617420919234
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of metallic ions onto activated carbon surface using computational chemistry software

Abstract: Activated carbon was prepared from the seeds of aguaje palm ( Mauritia flexuosa L.f.) by a chemical activation with phosphoric acid. This activated carbon was used for adsorbing metal ions: Pb(II), Cd(II), and Cr(III). To understand the mechanism of adsorption of these heavy metals (Cr, Cd, and Pb), the activated carbon surface was oxidized with nitric acid (1 M) increasing the oxygenated surface groups showing an increasing in their adsorption capacities of these metals. The oxidized activated carbon slightly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…The AC-treatment system exhibited removal efficiency above 80% for Ag, Pb, Cd, Co, Ni, and Ti and above 70% for Fe, Mg, and Zn, while Ca, Cr, and Mn were rejected below 50%. This validates that the AC is an excellent absorbent owing to its characteristics such as large surface area and the presence of functional groups such as quinone, carbonyl, lactone, phenol, and carboxyl. , It was reported that AC surfaces with large mesoporous areas exhibit relatively high adsorption capacity for some metal ions like Pd and Cd . The adsorption process could have been possible through ion exchange, acid–base, complexing metal ion, or surface precipitation of the AC surface and metal ions present in the wastewater .…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…The AC-treatment system exhibited removal efficiency above 80% for Ag, Pb, Cd, Co, Ni, and Ti and above 70% for Fe, Mg, and Zn, while Ca, Cr, and Mn were rejected below 50%. This validates that the AC is an excellent absorbent owing to its characteristics such as large surface area and the presence of functional groups such as quinone, carbonyl, lactone, phenol, and carboxyl. , It was reported that AC surfaces with large mesoporous areas exhibit relatively high adsorption capacity for some metal ions like Pd and Cd . The adsorption process could have been possible through ion exchange, acid–base, complexing metal ion, or surface precipitation of the AC surface and metal ions present in the wastewater .…”
Section: Resultssupporting
confidence: 53%
“…54 The adsorption process could have been possible through ion exchange, acid−base, complexing metal ion, or surface precipitation of the AC surface and metal ions present in the wastewater. 54 Based on the results obtained from the FTIR and SEM/EDX, the adsorption process that could have taken place in the current study is a complexing metal ion. The Z4 membrane filtration system exhibited similar removal capacity as the AC-treatment system except for Ca, Cr, and Mn, which have shown removal efficiencies between 50 and 65%.…”
Section: Rejection Of Multiple Metal Ionmentioning
confidence: 99%
See 1 more Smart Citation